2021
DOI: 10.3389/fchem.2021.756452
|View full text |Cite
|
Sign up to set email alerts
|

Polyprenylated Acylphloroglucinols With Different Carbon Skeletons From the Fruits of Garcinia multiflora

Abstract: Eleven new polycyclic polyprenylated acylphloroglucinols (PPAPs, 1–11) and three new monocyclic polyprenylated acylphloroglucinols (MPAPs, 12–14), together with ten known analogues were isolated from the fruits of Garcinia multiflora. These PPAPs belong to three types including the bicyclic polyprenylated acylphloroglucinols (BPAPs), the caged PPAPs, and the complicated PPAPs. Their structures and absolute configurations were determined through HRESIMS, NMR spectroscopy data, electronic circular dichroism (ECD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Comparison of the NMR data of compounds 5 and 6 with those of garcibracteatone and doitunggarcinone A revealed that compounds 5 and 6 contain ( E )-3-hydroxy-3-methylbut-1-en-1-yl groups at C-3, instead of a prenyl group at C-3 in garcibracteatone and doitunggarcinone, respectively. This was further confirmed by the HMBC correlations from H-14 and H-15 to C-3, , and the configuration of the double bond Δ 24(25) was assigned the E on the basis of the coupling constant value of 16.2 Hz between H-14 and H-15 . The relative configurations of 5 and 6 were also assigned as the same as those of compounds 2 – 4 based on the ROESY spectrum.…”
Section: Results and Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Comparison of the NMR data of compounds 5 and 6 with those of garcibracteatone and doitunggarcinone A revealed that compounds 5 and 6 contain ( E )-3-hydroxy-3-methylbut-1-en-1-yl groups at C-3, instead of a prenyl group at C-3 in garcibracteatone and doitunggarcinone, respectively. This was further confirmed by the HMBC correlations from H-14 and H-15 to C-3, , and the configuration of the double bond Δ 24(25) was assigned the E on the basis of the coupling constant value of 16.2 Hz between H-14 and H-15 . The relative configurations of 5 and 6 were also assigned as the same as those of compounds 2 – 4 based on the ROESY spectrum.…”
Section: Results and Discussionmentioning
confidence: 57%
“…This was further confirmed by the HMBC correlations from H-14 and H-15 to C-3, 11 , 12 and the configuration of the double bond Δ 24(25) was assigned the E on the basis of the coupling constant value of 16.2 Hz between H-14 and H-15. 17 The relative configurations of 5 and 6 were also assigned as the same as those of compounds 2 – 4 based on the ROESY spectrum.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Polyprenylated acylphloroglucinols were isolated from the fruits of Garcinia multiflora and their structure, together with absolute configuration determined by NMR, were supported using molecular modeling and GIAO calculations combined with the DP4þ methodology. 85 New debromoaplysiatoxin analogues 86 were isolated from marine Cyanobacterium Lyngbya sp. and their absolute configuration confirmed by X-ray studies and GIAO NMR calculations.…”
Section: Nuclear Shielding Prediction In Natural Productsmentioning
confidence: 99%